2017
DOI: 10.1016/j.redox.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of γ-glutamylcysteine increases intracellular glutathione levels above homeostasis in a randomised human trial pilot study

Abstract: ObjectiveTo determine if orally dosed γ-glutamylcysteine (γ-GC) can increase cellular glutathione (GSH) levels above homeostasis. Many chronic and age-related disorders are associated with down-regulation, or impairment, of glutamate cysteine ligase (GCL). This suggests that γ-GC supply may become limiting for the maintenance of cellular GSH at the normal levels required to effectively protect against oxidative stress and any resulting physiological damage.MethodsGSH levels were measured in lymphocytes of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 63 publications
0
45
0
6
Order By: Relevance
“…Besides NAC, γ‐glutamylcysteine, another GSH precursor, and 2‐oxothiazolidine‐4‐carboxylate (OTC), an analogue of 5‐oxproline, also seem to have the potential to increase endogenous GSH levels. Both γ‐glutamylcysteine and OTC increased GSH and reduced oxidative stress in experimental and clinical studies . Similar to NAC, supplementation of γ‐glutamylcysteine increased the levels of GSH in patients with cancer, with no adverse effects .…”
Section: The Future Of Oxidative Stress As a Therapeutic Target In Hementioning
confidence: 91%
See 1 more Smart Citation
“…Besides NAC, γ‐glutamylcysteine, another GSH precursor, and 2‐oxothiazolidine‐4‐carboxylate (OTC), an analogue of 5‐oxproline, also seem to have the potential to increase endogenous GSH levels. Both γ‐glutamylcysteine and OTC increased GSH and reduced oxidative stress in experimental and clinical studies . Similar to NAC, supplementation of γ‐glutamylcysteine increased the levels of GSH in patients with cancer, with no adverse effects .…”
Section: The Future Of Oxidative Stress As a Therapeutic Target In Hementioning
confidence: 91%
“…Both γ‐glutamylcysteine and OTC increased GSH and reduced oxidative stress in experimental and clinical studies . Similar to NAC, supplementation of γ‐glutamylcysteine increased the levels of GSH in patients with cancer, with no adverse effects . OTC, which is converted to cysteine by 5‐oxoprolinase (OPLAH), increased GSH levels in the experimental setting .…”
Section: The Future Of Oxidative Stress As a Therapeutic Target In Hementioning
confidence: 99%
“…Animal safety trials have demonstrated that GGC is safe at repeated doses at a limit dosage of 1000 mg/kg over a 90-day period [12]. No adverse effect was observed in a human clinical trial of healthy, non-fasting subjects [13]. Single dose of oral administered GGC at 2 g and 4 g is bioavailable and can increase intracellular GSH levels above homeostasis in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Products containing GGC for oral consumption are now on sale to the general public in the USA. An oral route of delivery allows for rapid first pass metabolism of GGC via the gut and liver and a subsequent increase in circulating GGC [13]. Defects in gut and liver function in CF patients, however, could hamper oral GGC efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation